The role of alkaline activator in geopolymerization of low-calcium fly ash based geopolymers - Omar, Abdul Kareem
Inorganic polymers or simply geopolymers were synthesized in this study by the alkaline activation of local low-calcium (Class F) fly ash. The alkaline activator liquid used for the activation process was a mixture of sodium silicate (waterglass) and sodium hydroxide (NaOH) solution. The main purpose of the research was to study the effect of the alkaline activator content and the alkaline activator constituents (Waterglass and NaOH solution) mixing ratio, on the compressive strength and on the microstructure of the resulted lowcalcium (Class F) Fly ash-based geopolymer. The geopolymers were prepared at fixed operation parameters, which were including: the concentration of NaOH solution (15M), additional water (17% of the geopolymer weight), mixing time (15min), dilation time (24hr), curing temperature (70°C), curing time (24hr), and aging time of (24hr). The alkaline activator content was verified according to the Activator/Fly ash mass ratios utilized in the current research, which were (0.3, 0.35, and 0.4), and verified the mixing ratios of the alkaline activator constituents or waterglass/NaOH ratios were (0.6, 0.8, 1.00, and 1.2). The highest compressive strength was obtained at highest alkaline activator content (Activator/Fly ash =0.4). The compressive strength and the SEM data also showed that for each Activator/Fly ash ratio (0.3, 0.35, and 0.4), an optimum waterglass/NaOH ratio of (0.8, 1.00, and 1.00 respectively); give the highest compressive strength and a homogenous, less porosity microstructure with less unreacted fly ash spheres. XRD analysis showed that the formed geopolymers at the optimum waterglass/NaOH ratios were mainly amorphous with presence of crystalline phases existed in the original fly ash and some zeolitic phases were formed during the geopolymerization process. The optimum compressive strength geopolymer (8.61 MPa, Activator/Fly ash ratio = 0.4, and waterglass/NaOH =1.00), shows low thermal durability at 400°C, by the formation of macrocracks on the sample surface due to the water evaporation and further deterioration and sintering process takes place at higher temperatures of 600 & 800°C.